Exploring Cost Savings with Specialty Biologic Drugs Administered to Adult Inpatients with Inflammatory Bowel Disease. (February 2022) - Pitman, Stuart; Jones, Carey; Polyak, Steven; Taylor, Alexandria; Cerven-Jenn, Diane; Reist, Diane
Background: Specialty infusion and self-injectable biologic drugs for the treatment of inflammatory bowel disease (IBD) are high-cost medications. When administered to hospital-admitted patients, these medications are not reimbursed on an individual basis but rolled into a per diem payment by most payers in the United States (US). Therefore, choosing to administer these medications in the inpatient setting may reveal negative financial implications for some health care institutions. Selecting an alternative site of care to administer these medications during the clinical management process may lead to cost savings.Objective: Review the clinical necessity of inpatient specialty biologic administrations for the treatment of IBD to identify and quantify potential cost saving opportunities.Methods: Using patient medical records at a US academic medical center, we retrospectively identified inpatient administrations of specialty infusion and self-injectable biologic medications for IBD treatment from June 1, 2016 to May 31, 2017. Guided by a standardized form, an evaluation team consisting of 3 of the investigators determined the clinical necessity of each specialty biologic medication administration within the inpatient setting. Costs and reimbursement rates for administration in both the inpatient and outpatient settings were procured and tabulated.Results: Seventeen inpatient specialty biologic administrations for IBD during the 12 month study period were identified. Of these, 11 administrations were given for the treatment of Crohn's disease (CD) and 6 for ulcerative colitis (UC). The evaluation team determined that 65% of these administrations were clinically necessary as inpatient administrations, and that 35% were not. The sum of the wholesale acquisition costs (WAC) for clinically necessary inpatient biologic administrations totaled $54 737, and the WAC for those administrations deemed not clinically necessary totaled $43 702. Further analysis of administration events revealed that the institution could have realized an estimated $13 817 in additional revenue above the cost of the drug if eligible inpatient biologic administrations had been received in the institution's outpatient clinic setting instead.Conclusion: Administering specialty biologic drugs for the treatment of IBD in the care setting best aligned with existing reimbursement structures may lead to institutional cost savings.